2012
DOI: 10.3855/jidc.1982
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enteropathogens in normal feces from healthy children at an infant day care in Brazil

Abstract: Introduction: The diarrhea associated with gastroenteritis is a major cause of morbidity and mortality worldwide, affecting mainly infants. The characterization of both viral and bacterial agents associated with gastroenteritis can establish policies for surveillance, prevention and treatment of infections. Group A rotaviruses are the major infectious agent associated with dehydration in children, followed by pathotypes of Escherichia coli. There are three main types of clinical infections caused by E. coli st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Huynen et al (2013) reported a similar prevalence of norovirus in both symptomatic and asymptomatic patients in Burkina Faso [22]. Enteric infections among apparently asymptomatic individuals represent a serious issue in endemic areas [23][24][25]. This unrecognized source of infections and the low level of hygiene and sanitation constitute a hazardous combination, which contributes to the endemic transmission of EE [7].…”
Section: Discussionmentioning
confidence: 99%
“…Huynen et al (2013) reported a similar prevalence of norovirus in both symptomatic and asymptomatic patients in Burkina Faso [22]. Enteric infections among apparently asymptomatic individuals represent a serious issue in endemic areas [23][24][25]. This unrecognized source of infections and the low level of hygiene and sanitation constitute a hazardous combination, which contributes to the endemic transmission of EE [7].…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli is a bacterium that is part of the gut microbiota of humans and animals, but some pathogenic strains can cause intestinal infections (diarrheagenic E. coli [DEC]) or extra-intestinal infections, such as meningitis and urinary infections (extraintestinal pathogenic E.coli [ExPEC]) (Croxen et al 2013;De Moura et al 2012;Nataro and Kaper 1998). The difference between indigenous and pathogenic strains is the presence of virulence factors in the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the epidemiological significance of EPEC and STEC as human pathogens, some individuals infected with these pathotypes show no apparent clinical signs of infection (De Moura et al ., 2012; Nunes et al, 2012). The presence of such pathogens in asymptomatic carriers is a public health concern because they act as reservoirs transmitting the disease throughout the community; however, little information is available about such cases.…”
Section: Introductionmentioning
confidence: 99%